Trichoderma reesei FS10-C enhances phytoremediation of Cd-contaminated soil by Sedum plumbizincicola and associated soil microbial activities - Teng, Ying; Luo, Yang; Ma, Wenting; Zhu, Lingjia; Ren, Wenjie; Luo, Yongming; Christie, Peter; Li, Zhengao (Frontiers in Plant Science, 2015)
This study aimed to explore the effects of Trichoderma reesei FS10-C on the phytoremediation of Cd-contaminated soil by the hyperaccumulator Sedum plumbizincicola and on soil fertility. The Cd tolerance of T. reesei FS10-C was characterized and then a pot experiment was conducted to investigate the growth and Cd uptake of S. plumbizincicola with the addition of inoculation agents in the presence and absence of T. reesei FS10-C. The results indicated that FS10-C possessed high Cd resistance (up to 300 mg L-1). All inoculation agents investigated enhanced plant shoot biomass by 6–53% of fresh weight and 16–61% of dry weight and Cd uptake by the shoots by 10–53% compared with the control. All inoculation agents also played critical roles in increasing soil microbial biomass and microbial activities (such as biomass C, dehydrogenase activity and fluorescein diacetate hydrolysis activity). Two inoculation agents accompanied by FS10-C were also superior to the inoculation agents, indicating that T. reesei FS10-C was effective in enhancing both Cd phytoremediation by S. plumbizincicola and soil fertility. Furthermore, solid fermentation powder of FS10-C showed the greatest capacity to enhance plant growth, Cd uptake, nutrient release, microbial biomass and activities, as indicated by its superior ability to promote colonization by Trichoderma. The solid fermentation powder of FS10-C might serve as a suitable inoculation agent for T. reesei FS10-C to enhance both the phytoremediation efficiency of Cd-contaminated soil and soil fertility.